2022
DOI: 10.1111/dom.14669
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mitochondrial‐targeted antioxidants on glycaemic control, cardiovascular health, and oxidative stress in humans: A systematic review and meta‐analysis of randomized controlled trials

Abstract: Aim: To investigate the effects of mitochondrial-targeted antioxidants (mitoAOXs) on glycaemic control, cardiovascular health, and oxidative stress outcomes in humans. Materials and Methods: Randomized controlled trials investigating mitoAOX interventions in humans were searched for in databases (MEDLINE-PubMed, Scopus, EMBASE and Cochrane Library) and clinical trial registries up to 10 June 2021. The Cochrane Collaboration's tool for assessing risk of bias and Grading of Recommendations, Assessment, Developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 42 publications
(229 reference statements)
0
9
0
Order By: Relevance
“…In general, low dietary intakes of antioxidant minerals and vitamins and a diet low in fruit and vegetables predict increased OS in adolescents and adults [ 66 , 67 , 68 ]. Increased OS is associated with metabolic risk factors and may contribute to the development of different comorbidities, including type 2 diabetes, cardiometabolic diseases, and atherosclerosis [ 8 , 69 , 70 , 71 ]. In addition, it has been found that similar to obese adults, obese children show a higher degree of OS than normal-weight children [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, low dietary intakes of antioxidant minerals and vitamins and a diet low in fruit and vegetables predict increased OS in adolescents and adults [ 66 , 67 , 68 ]. Increased OS is associated with metabolic risk factors and may contribute to the development of different comorbidities, including type 2 diabetes, cardiometabolic diseases, and atherosclerosis [ 8 , 69 , 70 , 71 ]. In addition, it has been found that similar to obese adults, obese children show a higher degree of OS than normal-weight children [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In cell culture, it reduced mitochondrial ROS production in HUVECs treated with plasma from PE patients. Both MitoQ and MitoTEMPO have been tested in humans and found to be tolerable with no adverse effect [ 162 , 163 , 164 , 165 ]. MitoQ has been reported to reduce liver inflammation in patients with chronic hepatitis C virus (HCV) infection [ 163 ].…”
Section: Potential For Mitochondrial Targeting Therapies In Preeclampsiamentioning
confidence: 99%
“…In another study, MitoTEMPO reduced mitochondrial ROS production in HUVECs treated with plasma from PE patients. Both MitoQ and mitTEMPO has been tested in humans and found to be tolerable with no adverse effect [153][154][155][156] . MitoQ has been reported to reduce liver inflammation in patients with chronic Hepatitis C Virus (HCV) infection [154].…”
Section: Mitoq and Mitotempomentioning
confidence: 99%